2018
DOI: 10.1371/journal.pone.0206361
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity assessed by genotyping by sequencing (GBS) and for phenological traits in blueberry cultivars

Abstract: Blueberry is a small fruit crop which includes a complex group of different Vaccinium species of various ploidy levels. Commercial blueberries have been grown in Europe most recently, so there is not much information available about their adaptation into new regions. In this work we investigated adaptation to the environmental conditions of northern Spain, in terms of flowering and ripening seasons, of a set of 70 blueberry cultivars including several of the most important cultivated American species (V. corym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…Results from the PCA indicated the absence of distinctive bioaccessibility features between the highbush blueberry and their hybrids (Supplementary Figure S7 ). These results are consistent with previous studies that NHB and SHB did not show distinctive features as evaluated by molecular markers or phenolic metabolite content 18 , 68 , 69 . The two highbush blueberry classifications, NHB and SHB, are commonly used in blueberry breeding programs for the improvement of agronomic and bioactive metabolite traits 24 , 70 .…”
Section: Resultssupporting
confidence: 93%
“…Results from the PCA indicated the absence of distinctive bioaccessibility features between the highbush blueberry and their hybrids (Supplementary Figure S7 ). These results are consistent with previous studies that NHB and SHB did not show distinctive features as evaluated by molecular markers or phenolic metabolite content 18 , 68 , 69 . The two highbush blueberry classifications, NHB and SHB, are commonly used in blueberry breeding programs for the improvement of agronomic and bioactive metabolite traits 24 , 70 .…”
Section: Resultssupporting
confidence: 93%
“…Similarly, NHB and SHB hybrids are very easy to obtain and are commonly used in breeding programs (Ballington, 2009;Hancock et al, 2018;Retamales and Hancock, 2018). Consistent with these observations, two independent studies (Campa and Ferreira, 2018;Zong et al, 2019) that used molecular markers to characterize blueberry germplasm revealed that the different ploidy (2×, 4×, 6×) were clearly differentiated, while SHB, NHB and half-highbush cultivars were not separated into different groups.…”
Section: Genotypic Effects Explain the Extensive Metabolite And Fruitmentioning
confidence: 52%
“…The sources of blueberry cultivars are complex, so clarifications by phylogenetic relationships are meaningful for the identification, protection and breeding of blueberry germplasm. Previous studies have used different molecular makers, including RAPD, SSR and SNP as a tool to construct the phylogenetic relationship of blueberry germplasm with different genetic origin [65][66][67][68][69]. In spite of the blueberry cultivars or breeding materials are from different origins or species with different ploidy levels, the SSR and SNPs marker seems to be an effective tool to differentiate and categorize blueberry cultivars [65,67,69].…”
Section: Genetic Relationships Among Blueberry Cultivarsmentioning
confidence: 99%
“…Previous studies have used different molecular makers, including RAPD, SSR and SNP as a tool to construct the phylogenetic relationship of blueberry germplasm with different genetic origin [65][66][67][68][69]. In spite of the blueberry cultivars or breeding materials are from different origins or species with different ploidy levels, the SSR and SNPs marker seems to be an effective tool to differentiate and categorize blueberry cultivars [65,67,69]. Here, we used single copy nuclear gene dataset to reconstruct the phylogenetic relationships of three blueberry species, and detected a good differentiation and grouping of blueberry cultivars with different origins.…”
Section: Genetic Relationships Among Blueberry Cultivarsmentioning
confidence: 99%